A review on green synthesis and recent applications of red nano Selenium - Pradnya B. Nikam; Jitendra D. Salunkhe; Tatiana Minkina; Vishnu D. Rajput; Beom Soo Kim; Satish V. Patil (2022)
As an essential micronutrient, the Selenium nanoparticles (SeNPs) are gaining much importance in therapeutics, agriculture, nutrient supplements, and antimicrobial agents. Different techniques can synthesize these SeNPs. Nowadays, biological synthesis is favored because it is environmentally safe, least toxic, more stable, and requires less energy. The whole microbial cells or their extracts with added Selenium oxyanions or selenium dioxides as the precursor synthesize SeNPs after incubation. The elemental Selenium (Se0) is significantly less toxic than its oxyanions, selenite, and selenate. Selenomethionine and selenocysteine are the primary organic forms of Selenium, involved in many proteins. Therefore, transforming these toxic materials into a biologically safe atomic structure becomes essential. Many microorganisms convert the environmentally available toxic Selenium oxyanions such as selenate or selenite into less toxic elemental Se nanoparticles (Se0). These microbes work as bio-nano-factories that utilize the Se anions into their metabolic pathways and detoxify them by forming the nanomaterial as the byproduct. In respiration, they may even use the selenite /selenate as a final electron acceptor. This review focuses on the biological methods for SeNps synthesis, using various microbes reported and their applications in different fields.